Assessing learning styles to improve skill development: a case study of NASSCOM. (2017) - Lele, Abhijeet; Nayak, Parameswar
The National Association of Software and Services Companies (NASSCOM) is the largest association of Indian information technology (IT) and information technology enabled services (ITeS) companies. Skill development is the biggest issue that the Indian software industry is facing at the moment. With ever-changing technological advancement and globalisation of business, the sector must develop the habit of exponential learning. But it is a gigantic task to bring change on such a scale where millions of people, coming from different culture, are involved. This case study unravels efforts from NASSCOM on skill development of workforce and challenges ahead in purview of Indian IT sector companies. In subsequent sections we have discussed challenges faced by NASSCOM and hidden reasons behind it. The case concludes with discussion on measure that NASSCOM should take to ensure better outcomes from skill development programs.